2020
DOI: 10.9734/ajopacs/2020/v8i130109
|View full text |Cite
|
Sign up to set email alerts
|

Batch Adsorption of Safranin Dye from an Aqueous Solution of Balanites aegyptiaca Seed Coats

Abstract: This study was aimed at using Balanite aegyptiaca seed coats activated carbon (BAAC) as a potential adsorbent to remove safranin dye from aqueous solution. BAAC was prepared from Balanite aegyptiaca seed coats using a one-step procedure with 67.27% yield, 3.23% ash content, 695 m2/g surface area and 203 mg/g iodine number. The FTIR spectroscopy revealed O-H, N-H, C-H, C=C, C-O-H stretching vibrations. The influences of agitation time, initial dye concentration and adsorbent dose were studied in batch experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Figure 10 displays the biosorption removal of CGR as follows: 73.5% on PWM at 125 rpm and 97.2% on its citric acid-modified form CPWM at 125 rpm, whereas 75.7% on native PWC at 125 rpm and 92.9% on its amended formulation at CPWC at 125 rpm, indicating the effective adsorption performance of chemically treated adsorbents as compared to their untreated forms. During the experiments, it was found that fast agitation speeds generated a thin layer of CGR molecules from the bulk on the surface interface of each adsorbent, which directly decreased the adsorption performance and increased the desorption of CGR [32]. The decrease in percentage adsorption of CGR at high agitation speeds of 125 rpm on CPWM and CPWC and 150 rpm on unmodified adsorbents PWM and PWC is also due to the fast and increased number of collisions of dye molecules on the adsorbent surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 10 displays the biosorption removal of CGR as follows: 73.5% on PWM at 125 rpm and 97.2% on its citric acid-modified form CPWM at 125 rpm, whereas 75.7% on native PWC at 125 rpm and 92.9% on its amended formulation at CPWC at 125 rpm, indicating the effective adsorption performance of chemically treated adsorbents as compared to their untreated forms. During the experiments, it was found that fast agitation speeds generated a thin layer of CGR molecules from the bulk on the surface interface of each adsorbent, which directly decreased the adsorption performance and increased the desorption of CGR [32]. The decrease in percentage adsorption of CGR at high agitation speeds of 125 rpm on CPWM and CPWC and 150 rpm on unmodified adsorbents PWM and PWC is also due to the fast and increased number of collisions of dye molecules on the adsorbent surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, 10 mL of each filtrate was titrated by using 0.1 M Na 2 S 2 O 3 as a standard solution, and the following equation was used to calculate the adsorbed iodine by each sample, PWM, and PWC: (7) Iodine number mg . g 1 = B S B × V . M W × 253.81 , where the molar mass of I 2 is 253.81 gmol -1 , W is the mass of adsorbent, and B is the volume of iodine solution without adsorbent sample, while S is the sample solution. V and M are volumes of filtrate and molar volume of I 2 solution, respectively [31, 32].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential application of Balanites aegyptiaca for removing water pollutants has been investigated recently. In this regard, activated carbon derived from Balanites aegyptiaca shells was successfully used for the adsorptive of methylene blue (Najem et al, 2019) and safranin dyes from the aqueous solutions (Magaji et al, 2020). In another study, untreated Balanites aegyptiaca seeds were used as a biosorbent for the removal of caffeine from the aquatic environment (N'diaye and Kankou, 2019).…”
Section: Introductionmentioning
confidence: 99%